Preferred Reporting Items for Resistance Exercise Studies (PRIRES): A Checklist Developed Using an Umbrella Review of Systematic Reviews - Ting-Yu Lin; Ting-Yu Chueh; Tsung-Min Hung (SpringerOpen, 2023)
Abstract Background The issues of replication and scientific transparency have been raised in exercise and sports science research. A potential means to address the replication crisis and enhance research reliability is to improve reporting quality and transparency. This study aims to formulate a reporting checklist as a supplement to the existing reporting guidelines, specifically for resistance exercise studies. Methods PubMed (which covers Medline) and Scopus (which covers Medline, EMBASE, Ei Compendex, World Textile Index, Fluidex, Geobase, Biobase, and most journals in Web of Science) were searched for systematic reviews that comprised the primary studies directly comparing different resistance training methods. Basic data on the selected reviews, including on authors, publication years, and objectives, were summarized. The reporting items for the checklist were identified based on the objective of the reviews. Additional items from an existing checklist, namely the Consensus on Exercise Reporting Template, a National Strength and Conditioning Association handbook, and an article from the EQUATOR library were incorporated into the final reporting checklist. Results Our database search retrieved 3595 relevant records. After automatic duplicate removal, the titles and abstracts of the remaining 2254 records were screened. The full texts of 137 records were then reviewed, and 88 systematic reviews that met the criteria were included in the umbrella review. Conclusion Developed primarily by an umbrella review method, this checklist covers the research questions which have been systematically studied and is expected to improve the reporting completeness of future resistance exercise studies. The PRIRES checklist comprises 26 reporting items (39 subitems) that cover four major topics in resistance exercise intervention: 1) exercise selection, performance, and training parameters, 2) training program and progression, 3) exercise setting, and 4) planned vs actual training. The PRIRES checklist was designed specifically for reporting resistance exercise intervention. It is expected to be used with other reporting guidelines such as Consolidated Standards of Reporting Trials and Standard Protocol Items: Recommendations for Interventional Trials. This article presents only the development process and resulting items of the checklist. An accompanying article detailing the rationale for, the importance of, and examples of each item is being prepared. Registration This study is registered with the EQUATOR Network under the title "Preferred Reporting Items for Resistance Exercise Studies (PRIRES)." PROSPERO registration number: CRD42021235259.